2005
DOI: 10.1177/014556130508400110
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Epley Maneuver for Posterior Canal BPPV: A Long-Term, Controlled Study of 81 Patients

Abstract: We assessed the efficacy ofthe Epley maneuver (canalith repositioning) in a study of 81 patients with posterior semicircular canal benign paroxysmal positional vertigo (BPPV). A group of61 patients underwent the maneuver; while a control group of20 patients received no therapy. All patients were evaluated at 1and 6 months. Thep ercentage ofpatients who experienced subj ective improvement was significantly high er in the treatment group at both 1 month (89% vs. 10%) and 6 months (92% vs. 50%). Three patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Our results are in line with those from a pilot study (comparing the Epley manoeuvre with no treatment) that we published some years ago . Epley's original study demonstrated a success rate of 97.7% .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in line with those from a pilot study (comparing the Epley manoeuvre with no treatment) that we published some years ago . Epley's original study demonstrated a success rate of 97.7% .…”
Section: Discussionsupporting
confidence: 90%
“…We know that spontaneous resolution of symptoms of BPPV is common, although percentages in the literature vary greatly. In a pilot study comparing the Epley manoeuvre with no treatment, we found 50% spontaneous resolution in the untreated group after 6 months (compared with 90% resolution in the Epley group) . One study found a percentage as high as 85% of symptom resolution in the control group after 3 months .…”
Section: Discussionmentioning
confidence: 90%
“…Two studies 12,14 provided information about symptom relief at longer term follow-up, namely, between 3 and 6 months. …”
Section: Long-term Follow-upmentioning
confidence: 99%
“…We will delay referral for medical review when the DHT converts to negative but the patient still feels slightly dizzy as most of these will resolve. The EM was first described in 1992 [7] and since then there has been a significant body of work reporting the success of the technique, including modifications, in the literature [6][7][8][9][10][11][12]. Prokopakis et al [6] reported their series of 592 patients treated by various canalith repositioning manoeuvres, in which 84% only required the manoeuvre to be performed once.…”
Section: Discussionmentioning
confidence: 99%
“…BPPV is treated by performing manoeuvres to reposition otoliths in the semicircular canals to the utricle [7,8]. The Epley manoeuvre (EM) and its modifications are effective in the treatment of posterior semicircular canal BPPV [6,[8][9][10][11][12]. The manoeuvre often needs to be repeated thereby necessitating subsequent follow-up appointments [6,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%